2017
DOI: 10.1371/journal.pone.0189598
|View full text |Cite
|
Sign up to set email alerts
|

Reference data on reaction time and aging using the Nintendo Wii Balance Board: A cross-sectional study of 354 subjects from 20 to 99 years of age

Abstract: BackgroundFalls among older adults is one of the major public health challenges facing the rapidly changing demography. The valid assessment of reaction time (RT) and other well-documented risk factors for falls are mainly restricted to specialized clinics due to the equipment needed. The Nintendo Wii Balance Board has the potential to be a multi-modal test and intervention instrument for these risk factors, however, reference data are lacking.ObjectiveTo provide RT reference data and to characterize the age-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The study indicated that the RT gets worse with age. [77] Consequently, the assessment and the modification of the risk are the mainstay of fall prevention in the elderly. [78] In this context, Bianco et al [79] showed that particular physical activity can influence (Dance and ballroom dancing) the RT and, ultimately, decrease the risk falls.…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that the RT gets worse with age. [77] Consequently, the assessment and the modification of the risk are the mainstay of fall prevention in the elderly. [78] In this context, Bianco et al [79] showed that particular physical activity can influence (Dance and ballroom dancing) the RT and, ultimately, decrease the risk falls.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these games are regarded as a reaction time exercises. Reaction time exercises essentially represent the cognitive-motor interaction, which is crucial for balance recovery (Blomkvist et al, 2017), and Wii Fit exergames may increase balance by reinforcing it.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed protocols for assessment of balance and reaction time are available elsewhere [28, 32], and reference data on reaction time can be found in a separate publication [29].…”
Section: Methodsmentioning
confidence: 99%
“…The method has a good validity when compared against the reference standards for HGS and LS [20, 23, 27]. It has also been shown to be valid for testing reaction time [28, 29], muscle force steadiness [30], and postural balance in younger [31] and older adults [32, 33]. Hence, the WBB has the potential to provide accurate assessment of several physiological measures, previously unavailable in a community setting.…”
Section: Introductionmentioning
confidence: 99%